2017
DOI: 10.1039/c7ra00682a
|View full text |Cite
|
Sign up to set email alerts
|

New insight into strong correlated states realised in a ferroelectric and paraelectric chalcogenide Sn2P2S6crystal

Abstract: The electronic properties of both the ferro and paraelectric phases of the Sn2P2S6 chalcogenide crystal were investigated using first principles methods. The Hubbard correction of the Hamiltonian was applied for this material for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For other ferroelectric chalcogenide semiconductor [17], it has been shown that the DFT+U approach [18] can lead to a correct description of energy bandwidth. Hence, we applied this approach for TlInS 2 .…”
Section: First-principle Calculation Results Of the Electronic Propermentioning
confidence: 99%
“…For other ferroelectric chalcogenide semiconductor [17], it has been shown that the DFT+U approach [18] can lead to a correct description of energy bandwidth. Hence, we applied this approach for TlInS 2 .…”
Section: First-principle Calculation Results Of the Electronic Propermentioning
confidence: 99%
“…The Hubbard correction is applied to all transition metals and to the main-group metals Ga and Pb, but it is not applied to Ca or Sr. We use the same value of U for all metals to which the Hubbard correction is applied; this value is chosen, as in some of our previous work, by considering the previous work that used PBE+U; on this basis, we chose 4 eV, and we apply this to the valence d band of transition metals and the valence p band of Ga and Pb.…”
Section: Computational Methodsmentioning
confidence: 99%
“…A theoretical confirmation of the formation of the conducting filaments, geometry optimizations and electronic density of states (DOS) was performed using a generalized gradient approximation, Hubbard parameters (GGA + U), and Perdew, Burke and Ernzerhof (PBE) functionals [44]- [46] to produce accurate calculation that include the Coulomb effect with non-local exchange and exchange correlation functionals. The values of the Hubbard parameters U for Zn and Sn were 5.0 eV [47] and 4.0 eV respectively, as reported in earlier findings [48]. All these calculations were carried out with the help of the Vienna ab initio simulation package (VASP) [49], [50] based on density functional theory.…”
Section: Theoretical Methodologymentioning
confidence: 99%